Fungsi Lembaga Adat Tongkonan Dalam Pelaksanaan Gadai Tanah Pertanian Di Toraja (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to determine how the function of the tongkonan traditional institution towards the implementation of pawning on agricultural land, to find out and analyze the factors that become obstacles to the implementation of pawning on agricultural land at the tongkonan customary institution. This type of research is a descriptive empirical legal research. Using qualitative and quantitative legal research approaches. The location of the legal research was conducted in Lemo Village, Makale Utara District, Tana Toraja Regency. Types and sources of legal research data include primary data and secondary data. Data collection techniques using literature study, interviews and questionnaires. Based on the results of research and discussion, the conclusion is that the function of the Tongkonan Traditional Institution for the implementation of pawning for agricultural land in Toraja is as a bridge as well as a link between the pawner and the pawner recipient, the Tongkonan Traditional Institution also functions for the welfare of the community with the value of the customary law order, preserving customs and culture. The factors inhibiting the implementation of pawning of agricultural land at the tongkonan customary institution in Toraja are that the community prefers to mortgage their agricultural land directly without involving the tongkonan customary institution again as a witness, the next factor is the agreement between families, because most agricultural land owned by the Toraja community is family land.